Fish Oil, Cannabidiol and the Gut Microbiota: An Investigation in a Murine Model of Colitis - Silvestri, Cristoforo; Pagano, Ester; Lacroix, Sébastien; Venneri, Tommaso; Cristiano, Claudia; Calignano, Antonio; Parisi, Olga A.; Izzo, Angelo A.; Di Marzo, Vincenzo; Borrelli, Francesca (Frontiers in Pharmacology, 2020)
In experimental colitis, administration of fish oil (FO) and the non-psychoactive cannabinoid, cannabidiol (CBD) reduces inflammation and ameliorates behavioural disturbances, two conditions associated with alterations in the gut microbiota (dysbiosis). We investigated the effect of combined FO/CBD administration on inflammation and dysbiosis in the dextran sulphate sodium (DSS) model of mouse colitis, which also causes behavioural disturbances. Colitis was induced in CD1 mice by 4% w/v DSS in drinking water for five consecutive days followed by normal drinking water. FO (20-75 mg/mouse) was administered once a day starting two days after DSS, whereas CBD (0.3-30 mg/kg), alone or after FO administration, was administered once a day starting three days after DSS, until day 8 (d8) or day 14 (d14). Inflammation was assessed at d8 and d14 (resolution phase) by measuring the Disease Activity Index (DAI) score, change in body weight, colon weight/length ratio, myeloperoxidase activity and colonic interleukin (IL)-1β (IL-1β), IL-10 and IL-6 concentrations. Intestinal permeability was measured with the fluorescein isothiocyanate-dextran. Behavioral tests (novel object recognition (NOR) and light/dark box test) were performed at d8. Fecal microbiota composition was determined by ribosomal 16S DNA sequencing of faecal pellets at d8 and d14. DSS-induced inflammation was stronger at d8 and accompanied by anxiety-like behaviour and impaired recognition memory at d8. FO (35, 50, 75 mg/mouse) alone reduced inflammation at d8, whereas CBD alone produced no effect at any of the doses tested; however, when CBD (3,10 mg/kg) was co-administered with FO (75 mg/mouse) inflammation was attenuated. FO (20 mg/mouse) and CBD (1 mg/kg) were ineffective when given alone, but when co-administered reduced all inflammatory markers and the impaired intestinal permeability at both d8 and d14 (but not the behavioural impairments). FO, CBD and their combination affected gut bacteria taxa that were not affected by DSS per se. Akkermansia muciniphila, a species suggested to afford anti-inflammatory action in colitis, was increased by DSS only at d14, but its levels were significantly elevated by all treatments at d8. FO and CBD co-administered at ineffective doses reduce colon inflammation, in a manner potentially strengthened by their independent elevation of Akkermansia muciniphila at d8.